A case control study to determine the association between Perthes' disease and the recalled use of tobacco during pregnancy, and biological markers of current tobacco smoke exposure. (August 2017) - Perry, D. C.; Thomson, C.; Pope, D.; Bruce, C. E.; Platt, M. J.
Abstract : Aims: It is well established that there is a strong association between Perthes' disease and worsening socioeconomic deprivation. It has been suggested that the primary determinant driving this association is exposure to tobacco smoke. This study aimed to examine this hypothesis. Patients and Methods: A hospital case-control study (n = 149/146) examined the association between tobacco smoke exposure and Perthes' disease, adjusting for area-level socioeconomic deprivation. Tobacco smoke exposure was assessed by parental questionnaire of smoking habits during pregnancy, and by quantitative assay of current exposure using the urinary cotinine-creatinine ratio, which is a widely used and validated measure of tobacco smoke exposure. Results: The odds of Perthes' disease significantly increased with reported in utero exposure after adjustment for socioeconomic deprivation (maternal smoking odds ratio (OR) 2.06, 95% confidence interval (CI) 1.17 to 3.63; paternal smoking OR 2.09, 95% CI 1.26 to 3.46). The cotinine-creatinine ratio was significantly greater in cases, OR 1.63 (95% CI 1.09 to 2.43), suggesting a greater 'dose' of current tobacco exposure. Conclusion: An association exists between tobacco smoke exposure and Perthes' disease but we remain unable to disentangle the association with socioeconomic deprivation. Cite this article: Bone Joint J 2017;99-B:1102–8.